The Comparıson Of The Tmj Functıons In Chıldren Wıth Class I, Class Ih And Class Iıı Malocclusıons - Elif Erbay; Cüneyt Keskin; Şevket Erbay; Gülnaz Marşan; Didem Güner (Galenos Yayinevi, 2003)
The aim of this study is to investigate the TMJ functions clinically and axiographically and to compare the findings in untreated Class I, Class II-1 and Class III subjects in the permanent dentition. 40 children who had no TMJ dysfunction symptoms clinically were investigated. In the Class I group, there were 12 children (mean age:12.89 years ), in the Class II-1 group, 17 children (mean age: 12.83 years), in the Class III group II children (mean age: 13.68 years). 8 angular, 8 linear parameters were measured on lateral cephalograms of each group. After the clinic examination of each subject, the amount of maximum protrusion and the maximum capacity of mouth opening were measured by using a compass and the movements of maximum protrusion and mouth opening were investigated by using axiograph for right and left TMJ's separetely. For the evaluation of axiographic records, the mean values of the right and left TMJ's were used. The differences between the Class I, Class II-1 and Class III groups were compared by using Mann Whitney U-Test. The results of this study showed that; clinically, the amount of maximum protrusion was found greater in the Class II-1 group than in the other two groups. As a clinical observation, the amount of maximum mouth opening was found greater in the Class II-1 group than in the Class III group. The axiographic results showed that; the dimension of the protrusive mouth opening-closing line was greater in the CI II-1 group than in the CI III group, the value of the beginning angle of protrusion line was greater in the CI III group than in the CI I group, the differentiation angle of the mouth opening-closing movement was greater in the CM II group than in the other groups, the dimensional differentiation of the protrusion line was greater in the CI III group than in the CI I group, the dimensional differentiation of the opening-closing line was greater in the CI III group than in the other groups.